Bank Debt Restructurings and the Composition of Exchange Offers in Financial Distress - JAMES, CHRISTOPHER (Journal of Finance, 1996)
ABSTRACT This article examines the relation between bank debt forgiveness and the structure of public debt exchange offers in financial distress. I find that the structure of exchange offers and the likelihood of an offer's success are significantly related to whether the bank participates in the restructuring transaction. Exchange offers made in conjunction with bank concessions are characterized by significantly greater reductions in public debt outstanding and significantly less senior debt offered to bondholders. Overall, the results suggest that the structure of a firm's public and private claims significantly affects the firm's ability to modify its capital structure in financial distress.